2380. Healthcare Resource Utilization for High-Risk Patients Treated With Dalbavancin in Physician Office Infusion Centers (POICs). (26th November 2018) - Luu, Quyen; Statner, Barry; Dretler, Robin H; Baker, H Barry; Metzger, Brian S; Hardin, Thomas C; Schroeder, Claudia P; Van Anglen, Lucinda J
Abstract: Background: Medicare beneficiaries and patients (patients) ≥65 years comprise the highest risk for utilization of healthcare resources including emergency department (ED) visits and hospitalizations (hosp). Dalbavancin (DAL) is a long-acting lipoglycopeptide approved for treatment of bacterial skin and skin structure infections, well suited for outpatient therapy due to a 1–2 dose regimen. We investigated the use of healthcare resources following DAL with associated costs compared with national data. Methods: A multi-center, retrospective chart review was conducted of all high-risk patients receiving DAL during 2017 at participating sites. Data included demographics, diagnosis, Charlson index, prior/post-IV therapies, DAL regimen, and adverse drug reactions (ADRs). ED visits and hosp within 30 days post-DAL were assessed and compared with Healthcare Cost and Utilization Project Nationwide Inpatient Sample and Nationwide Emergency Department Sample stratified by diagnosis. The inpatient length of stay (LOS) was used to calculate hospital charges. Results: DAL was administered to 124 patients (mean age: 71 ± 10 years, mean Charlson index of 4.6, 55% male) in 10 POICs. Most patients (92%) received a 1-dose regimen. Diagnoses included cellulitis (32%), abscess (22%), diabetic foot infection (15%), osteomyelitis (10%), surgical site infections (9%), prosthetic device infection (9%), and musculoskeletal infections (3%). 55% were treated from the community. IV therapy with other agents was provided prior to DAL in 58% and following DAL in 6%. Moderate to severe ADRs were seen in 12 patients (10%) with 4 admitted to the ED and 3 hosp. Median onset of ADRs was 5 days post DAL. All cause ED visits were 10 (8%), compared with a national rate of 10.6% based on diagnosis and age ≥65. All cause 30-day hosp admissions were 11.3% (14/124) compared with a national rate of 16.1% based on diagnosis. Mean inpatient LOS was 4.9 days compared with 5.3 days, resulting in healthcare resource cost savings of 97, 014. Conclusion: Use of DAL in high-risk, comorbid patients treated in POICs was associated with lower usage of both healthcare resources and corresponding costs than national estimates for respective diagnoses. AEs contributed to healthcare resource use. DAL provides a convenient outpatient treatment option for high-risk patients that may save use of healthcare resources. Disclosures: R. H. Dretler, BMS: Grant Investigator, Research grant. Gilead: Grant Investigator, Research grant. Janssen: Grant Investigator, Research grant. Merck & Co.: Grant Investigator, Research grant. Viiv: Grant Investigator, Research grant. B. S. Metzger, Allergan: Speaker's Bureau, Speaker honorarium. L. J. Van Anglen, Merck & Co.: Grant Investigator, Research grant.